(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2026)
This article examines the primary methods of noun formation in the Uzbek and Russian languages. Particular attention is devoted to a comparative analysis of word-formation models, given that Uzbek and Russian belong to distinct linguistic systems: Uzbek is an agglutinative language, while Russian is an inflectional one. The study analyzes suffixation, prefixation, combined prefixation-suffixation, compounding, and zero derivation as methods of noun formation. Based on specific examples, the commonalities and distinctive features of word formation in the two languages are identified. The research results indicate that in Uzbek, affixation—specifically suffixation—plays a leading role; conversely, in Russian, prefixation, combined prefixation-suffixation, and zero derivation function actively alongside suffixation. A comparative study of these languages holds significant importance for linguistics, translation studies, and the methodology of teaching Russian and Uzbek.